Deposit insurance as private club : is Germany a model? - Beck, Thorsten, 1967- 1967- (Policy research working paper, 2001)
Germany's private deposit insurance scheme with its "clublike" nature, cannot easily be transplanted to countries with weaker institutions. But it offers useful lessons for countries that want to set up a new scheme or reform an existing one